A forma jurídica no capitalismo dependente - Souza, Yago Renan Licarião de (2019)
The marxist critic of law imputed by Evgeni Pachukanis changed the way of seeing the juridical phenomenon, to bring from marxian theory sufficient elements to point that, instead of a neutral instrument of classist domination, the juridical form is presented as a specific social relationship, directly related to the merchandise-form. His position occurs in clear confrontation with juspositivist theories, marked by the identification of the law with state rules, and the nonjuspositivists theories, who identifies the law with power relations, and enshrines the understanding that the juridical form has its birth in an established relationship between subjectowners who, in order to establish the exchange of goods, also need to identify themselves as equivalent, equal, and perform that act in full freedom of choice. However, when using this theory in the study of distinct social realities, such as the periphery of capitalism, one must take into account the specificities of dependent capitalism, a socioeconomic system that has unique characteristics in its structure and which can be summarized in the mechanisms of value transfer and in unequal exchanges that impose the distribution of the economic surplus produced internally to the central economies through international trade; the overexploitation of the labor force, which is used in a structural way to compensate for the losses of value occurred in the circulation, impose on the working class the premature consumption of its productive capacity through the under-remuneration of the value of its workforce, aggravating the conditions of inequality within these societies and confirming a split cycle of capital, in which domestic production has, as objective, to realize the circulation, mostly, in the external market, eliminating workers from the consumer market itself and preventing the advance of these productive forces to a self-directed development. All these questions, when combined, lead to the theoretical effort to undertake approximations between the reality of dependent capitalism and its implications in the juridical form developed in its interior, in order to identify the possibility of a dependent juridical form that establishes within institutional structures of weak character and that can be identified in the normative instruments that explain the conditions of reproduction of dependence.